Healthcare in the Anthropocene: Challenges and Opportunities - Trevor Hancock (Healthcare Quarterly, 2016)
We are entering the Anthropocene. So large is our impact on the planet that Earth scientists suggest our presence will show up in the geologic record far into the future. The global ecological changes we are creating pose a threat to health not only from climate change but from pollution and ecotoxicity, ocean acidification, resource depletion and the loss of biodiversity that threatens a sixth "Great Extinction." These health threats will impose an added burden on the healthcare system, while the ecological changes will force it to adapt to the new realities. The healthcare system contributes to these changes. It is an energy and resource-intensive part of society that also produces large volumes of solid and liquid wastes and air pollutants, some of them quite toxic; the system has a large ecological footprint; yet, at the same time, the system has an ethical duty to do no harm, and thus should be a leader in the transition to a more ecologically sustainable and healthier future.
Keywords: Green healthcare, climate change, ecologically sustainable, environmentally sustainable, environmental impact, sustainable recycling